UR PROSES PENANGANAN LOIN IKAN TUNA DI PT MARITIME TIMUR PERKASA KOTA KUPANG - Syifa Rachmatika Sukandi; Herning Pramudya; Wanri Sitanggang; Safingi Alamsah; Muhammad Afrisal; Masrurah Ismail; Raymundus Putra Situmorang; Moh. Ramadan Daud; Muhammad Reiza Aqilla Gunawan; Kleopas Raimundus Seran; Reyhan Zain; Daniel Candido Da Costa Soares (Universitas Mataram, 2025)
The handling of tuna loin, starting from the receiving process to the packaging stage (packing), is a critical series in maintaining the quality and safety of fishery products. This study aims to describe the process flow of tuna loin handling at PT Maritim Timur Perkasa, Kupang City, starting from the receipt of raw materials to the final packaging, the methods used in this study are direct observation of the production flow, interviews with operational staff, and recording the temperature conditions and handling time of each stage. The results of this study indicate that the tuna received is immediately checked for quality and trimming and retouching are carried out to separate good meat from unwanted meat. These loin pieces are then frozen in an Air Blast Freezer to a temperature of around -40 degrees Celsius, which is then packaged using food-grade materials with a quality label and production date and then stored in cold storage at a temperature of -20 degrees Celsius until the shipping process. Handling accompanied by quality control at every stage of processing and handling will provide good quality products.